Improvement of the Bias Stress Stability in 2D MoS(2) and WS(2) Transistors with a TiO(2) Interfacial Layer - Park, Woojin (Nanomaterials (Basel), 2019)
The fermi-level pinning phenomenon, which occurs at the metal–semiconductor interface, not only obstructs the achievement of high-performance field effect transistors (FETs) but also results in poor long-term stability. This paper reports on the improvement in gate-bias stress stability in two-dimensional (2D) transition metal dichalcogenide (TMD) FETs with a titanium dioxide (TiO(2)) interfacial layer inserted between the 2D TMDs (MoS(2) or WS(2)) and metal electrodes. Compared to the control MoS(2), the device without the TiO(2) layer, the TiO(2) interfacial layer deposited on 2D TMDs could lead to more effective carrier modulation by simply changing the contact metal, thereby improving the performance of the Schottky-barrier-modulated FET device. The TiO(2) layer could also suppress the Fermi-level pinning phenomenon usually fixed to the metal–semiconductor interface, resulting in an improvement in transistor performance. Especially, the introduction of the TiO(2) layer contributed to achieving stable device performance. Threshold voltage variation of MoS(2) and WS(2) FETs with the TiO(2) interfacial layer was ~2 V and ~3.6 V, respectively. The theoretical result of the density function theory validated that mid-gap energy states created within the bandgap of 2D MoS(2) can cause a doping effect. The simple approach of introducing a thin interfacial oxide layer offers a promising way toward the implementation of high-performance 2D TMD-based logic circuits.